From Public Lectures to Supervised Practical Work: Learning the Social Work Craft at the School of Social Service of Santa Fe in the 1940s and 1950s (Papeles, 2025)
In Social Work, the tradition of practical training which allows one to learn the craft and the "know-how" of the profession, began early on. At the Santa Fe School of Social Service, this was incorporated into the curriculum from the creation of the program, with the requirement to engage in activities outside the classroom and the involvement of external actors. In this article, I aim to reconstruct the various modalities outlined in the five curricula in effect from 1943 to 1959, map the institutions where the practical training experiences took place, and analyze the teaching through supervision.In the case under analysis, this training was organized with different modalities, including lectures, institutional visits and stays, participation in the creation of institutions, and the organization of social services. The transmission of the craft by professionals from the Social Welfare institutions, guided reading, and supervision meetings are presented as constants. There are documents that support this discussion and make it possible to analyze the assumptions on which the different modalities were based: curricula, regulations, local and international documents.
Keywords: social work; professionalization; teaching; practical training; supervision